(3TQM GdebQHs - (3CHhYHO Gddg HgGA GdOjf eMeO Hf EHQGgje Hf eMeO Hf GdfMGS GdMdHjs; (3GHf YUahQ , Ydj Hf eDef Hf eMeO GdMVQej GdGTHjdj, CHh GdMSf,J (B669 (3g` s
(3ChdgG (B:s
(3bhdg(B: (3GdMeO ddg GdPj de jSJaJM HCaVd ef GSeg cdGe GdMeO(B: (3GdKfGA Ydi GdeeOhM s
(3BNQgG (B:s
(3hEfeG gh eKd eSjWQ, aEf bjd gPG eG hLO ef gPG GdJYdjb dGHf GdfMGS QMeg Gddg s
(3fSNI JYGhQ YdjgG fGSNGfs
(3HgG fXGe GdJYbjHIs
(3HChdgG Jedc ddTjN MSf GdYWGQ Ke hbag EjGgG Ydi WdHI GdCRgQ hLYdg QhGb GdeZGQHI ebQkG dgGs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdfMhs